The Semantic Evolution of Selected Terms Related to Writing and Its Essentials in al-Muʿjam al-Wasīṭ: Review and Study - Albalawi, Awatif Farah (Arts for Linguistic & Literary Studies, 2024)
This study aims to explore the semantic evolution of terms related to writing in al-Mu'jam al-Wasīt, employing a historical approach. The research is divided into two main sections. The first section deals with the theoretical aspect. It discusses the concept of semantic evolution, its causes and manifestations, and highlights examples of semantic shifts in the Arabic language throughout history. The second section, the practical aspect, focuses on words associated with writing and their related terms in al-Mu'jam al-Wasīt. The study reveals several key findings, most notably that the word for "writing"—originally meaning "to seal the opening of a waterskin with a strap to prevent water from escaping"—has shifted far from its linguistic roots to its current meaning of recording and writing. Over time, the original meaning has faded, and the newer usage has become dominant. Additionally, the meanings of some words continue to evolve with the progress of life and the increasing need for writing and its tools, such as the pen.